Analysis of Drought in the Sekayam Watershed during a Very Strong El Niño Event (1997) - Ajeng Candra Indrawati; Andi Ihwan; Riza Adriat (Sam Ratulangi University, 2024)
Low rainfall and limited surface water availability during El Niño events leave significant portions of Indonesia highly susceptible to drought. As a mitigation strategy to address the impacts of the El Niño phenomenon, a comprehensive analysis of drought characteristics in affected regions is essential. This study aims to assess the characteristics of meteorological drought using the Standardized Precipitation Index (SPI) method, and hydrological drought through the Standardized Streamflow Index (SSI) method, within the Sekayam Watershed. The data utilized in this study includes rainfall and streamflow data from the period of the exceptionally strong El Niño event in 1997.The findings indicate that meteorological drought in the Sekayam Watershed was predominantly classified as moderately dry, with the most severe drought conditions observed in January, March, and December, affecting a small portion of the upstream area of the watershed. In contrast, hydrological drought was primarily categorized as dry, with the most severe conditions occurring in July. Moreover, the correlation between SPI and SSI during the 1997 El Niño event was found to be strong, with a correlation coefficient of 0.77. Keywords: Rainfall; drought; el niño; standardized precipitation index